# Use special products to expand and simplify (2 + 2a)^6Show complete process and solution.

*print*Print*list*Cite

Expert Answers

sciencesolve | Certified Educator

You could consider (2 + 2a)^6 = [(2 + 2a)^3]^2

Use the formula of binomial raised to cube:

(x+y)^3 = x^3 + 3x^2y + 3xy^2 + y^3

Use this formula to expand (2 + 2a)^3:

(2 + 2a)^3 = 2^3 + 3*4*2a + 3*2*4a^2 + 8a^3

(2 + 2a)^3 = 8 + 24a + 24a^2 + 8a^3

(2 + 2a)^3 = 8*(1+a^3) + 24a(1+a) = 8(1+a)(1 - a + a^2 + 3a)

(2 + 2a)^3 = 8(1+a)(a^2 + 2a + 1)

Use the special product (a+1)^2 instead of a^2 + 2a + 1.

(2 + 2a)^3 = 8(1+a)(1+a)^2 = 8(1+a)^3

Calculate (2 + 2a)^6 = [(2 + 2a)^3]^2 = [8(1+a)^3]^2 = 64(1+a)^6

**Therefore, (2 + 2a)^6 = 64(1+a)^6**